2023
DOI: 10.3390/vaccines11020336
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of SARS-CoV-2 Seroprevalence: A Snapshot among the General Population in Kuwait

Abstract: We sought to assess pre-vaccination and post-vaccination seroprevalences of anti-SARS-CoV-2 antibodies in Kuwait and to compare antibody levels between vaccine types. In phase 1 (pre-vaccination period, n = 19,363), blood samples were collected before the launch of COVID-19 vaccination in Kuwait between 1 September and 31 December 2020. Blood samples for phase 2 (post-vaccination period, n = 4973) were collected between 1 September and 30 November 2021. We tested subjects for anti-SARS-CoV-2 antibodies using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In Canada, also during the pre-vaccine period, a prevalence of 4.6% was found ( 22 ), while in Brazil around the same period, a seroprevalence of 25.4% was found ( 23 ). For the eastern region of the world, a study conducted in Kuwait found a seroprevalence of 24.8% ( 24 ). In more general terms, a meta-analysis was conducted on articles from 88 countries, namely, original articles published from December 2019 to December 2021, and it was concluded that the pooled estimate of seroprevalence SARS-CoV-2 was 15% in Eastern Mediterranean countries, 6% in Africa, 8% in the Americas, 5% in Europe, and 3% in the Western Pacific ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, also during the pre-vaccine period, a prevalence of 4.6% was found ( 22 ), while in Brazil around the same period, a seroprevalence of 25.4% was found ( 23 ). For the eastern region of the world, a study conducted in Kuwait found a seroprevalence of 24.8% ( 24 ). In more general terms, a meta-analysis was conducted on articles from 88 countries, namely, original articles published from December 2019 to December 2021, and it was concluded that the pooled estimate of seroprevalence SARS-CoV-2 was 15% in Eastern Mediterranean countries, 6% in Africa, 8% in the Americas, 5% in Europe, and 3% in the Western Pacific ( 25 ).…”
Section: Discussionmentioning
confidence: 99%